Expression of matrix metalloproteinases in patients with bipolar disorder - Fábria Chiarani; Gabriel Rodrigo Fries; Laura Stertz; Keila Maria Ceresér; Angela T.S. Wyse; Flávio Pereira Kapczinski; Maurício Kunz (Brazilian Journal of Psychiatry, 2013)
Objective: High cardiovascular mortality rates have been reported in patients with bipolar disorder (BD). Studies indicate that matrix metalloproteinases (MMPs) are implicated in cardiovascular diseases. We evaluated the expression pattern of MMP-2 and MMP-9 in blood from patients with BD during acute mania and after euthymia, in comparison with healthy controls. Methods: Twenty patients and 20 controls were recruited and matched for sex and age. MMP messenger RNA (mRNA) levels were measured using real-time quantitative polymerase chain reaction (PCR). Body mass index (BMI) was calculated for all subjects. Results: There were no significant differences in MMP-2 and MMP-9 mRNA expression between patients and controls. mRNA levels were not significantly different during mania and euthymia. However, MMP-2 mRNA levels were negatively associated with BMI in BD patients and positively associated with BMI in controls. There was no difference in the pattern of MMP-9 expression between patients and controls. Conclusions: Our results suggest a different pattern of association between MMP-2 and BMI in BD patients as compared with controls. Despite some study limitations, we believe that the role of MMPs in BD should be further investigated to elucidate its relationship with cardiovascular risk.